HPLC-PDA combined with chemometrics for chemical markers of Paeoniae Radix Alba before and after sulfur-fumigated - Xiaozhou Jia (Results in Chemistry, 2021)
To quantitatively compare the chemical composition of Paeoniae Radix Alba before and after sulfur-fumigated by using HPLC fingerprint and chemometrics, to provide a reference for the quality evaluation of Paeoniae Radix Alba. Establish the fingerprints of 9 batches of white peony and its sulfur-fumigated products, combined with orthogonal partial least squares-discriminant analysis (PLS-DA) to compare the composition differences of white peony before and after sulfur-fumigation. For the quantitative analysis of sexual components, differential compounds were identified by UPLC-MS. The contents of gallic acid, catechins, albiflorin, paeoniflorin, 1,2,3,4,6-pentagalloyl glucose and benzoylpaeoniflorin before and after sulfur-fumigation Paeoniae Radix Alba were determined, and there were 6 common peaks in the HPLC fingerprints of Paeoniae Radix Alba before and after sulfur-fumigated. There were 6 common peaks in Paeoniae Radix Alba without sulfur-fumigated, and 7 peaks after sulfur-fumigated. The differential compound (peak 7) was proven to be paeoniflorin sulfite.The differential compound was proven to be paeoniflorin sulfite. This method can be used for fingerprint analysis and quantitative analysis of different components of Paeoniae Radix Alba and sulfur-fumigated Paeoniae Radix Alba, and can distinguish Paeoniae Radix Alba from sulfur-fumigated Paeoniae Radix Alba.